Faktor-Faktor Yang Mempengaruhi Tax Avoidance Perusahaan Industri Barang Konsumsi - Reynaldo Christie, Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to obtain empirical evidences on the influence of sales growth and good corporate governance toward tax avoidance on consumer goods indutry manufacturing companies that listed in Indonesia Stock Exchange (BEI) over the period 2012-2018, with the total of 21 sample companies. This study use secondary data which were processed using IBM SPSS Statstics 22 and SmartPLS 3 softwares. The result of this study suggests that sales growth does not has significant influence to tax avoidance. However, good corporate governance influence tax avoidance significantly and negatively.